PERTANGGUNGJAWABAN PIDANA TERHADAP PELAKU TINDAK PIDANA KORUPSI DALAM BENTUK SUAP (STUDI KASUS PUTUSAN PENGADILAN NEGERI JAKARTA PUSAT NOMOR 77/PID.SUS-TPK/2023/PN.JKT.PST - Rohadi, Rohadi; Heliany, Ina (Postulat, 2024)
Offering or promising something to a person with the intention of influencing them to perform or refrain from performing a duty contrary to their authority or obligation in the public interest is known as bribery. According to the Corruption Crime Act, any gift given to a state official or civil servant is considered a bribe. This research focuses on the legal liability of state officials who accept gifts and the factors considered by judges in deciding cases involving corrupt officials who receive gifts, as seen in the Central Jakarta District Court Decision Number 77/Pid.Sus-TPK/2023/PN Jkt.Pst. The findings of the study indicate that gratuities given to state officials or civil servants are deemed bribes if they are related to their position and contradict their duties or obligations. The first provision requires proof that the gratuity is not a bribe, while the second provision requires proof that the gratuity is valued at less than Rp10,000,000.00. The prosecutor provided evidence that the gifts in question constituted bribes. Failing to report the received benefits can result in fines of at least Rp200,000,000.00 (two hundred million rupiah) and up to Rp1,000,000,000.00 (one billion rupiah), as well as imprisonment for a minimum of 4 years and a maximum of 20 years or life imprisonment. The bribe giver may also face fines of at least Rp50,000,000.00 (fifty million rupiah) and up to Rp250,000,000.00 (two hundred fifty million rupiah), and imprisonment for a maximum of one to five years. Article 13 of Law No. 31 of 1999 on the Eradication of Corruption Crimes also includes additional penalties, such as fines of up to Rp150,000,000.00 (one hundred fifty million rupiah) and/or imprisonment for up to 3 years. In decision number 77/Pid.Sus-TPK/2023/PN Jkt.Pst, the judge considered the degree of culpability, the charges under Article 12(b) in conjunction with Article 18 of Law No. 31 of 1999 on the Eradication of Corruption Crimes, as amended by Law No. 20 of 2001 concerning Amendments to Law No. 31 of 1999, in conjunction with Article 55 Paragraph (1) of the Penal Code and Article 64 Paragraph (1) of the Penal Code, as well as aggravating and mitigating factors.